The Rab5 Guanine Nucleotide Exchange Factor Rabex-5 Binds Ubiquitin (Ub) and Functions as a Ub Ligase through an Atypical Ub-interacting Motif and a Zinc Finger Domain - Mattera, Rafael; Tsai, Yien Che; Weissman, Allan M.; Bonifacino, Juan S. (The Journal of biological chemistry, 2006)
Rabex-5, the mammalian orthologue of yeast Vps9p, is a guanine nucleotide exchange factor for Rab5. Rabex-5 forms a tight complex with Rabaptin-5, a multivalent adaptor protein that also binds to Rab4, Rab5, and to domains present in γ-adaptins and the Golgi-localized, γ-ear-containing, ARF-binding proteins (GGAs). Rabaptin-5 augments the Rabex-5 exchange activity, thus generating GTP-bound, membrane-associated Rab5 that, in turn, binds Rabaptin-5 and stabilizes the Rabex-5·Rabaptin-5 complex on endosomes. Although the Rabex-5·Rabaptin-5 complex is critical to the regulation of endosomal fusion, the structural determinants of this interaction are unknown. Likewise, the possible binding and covalent attachment of ubiquitin to Rabex-5, two modifications that are critical to the function of yeast Vps9p in endosomal transport, have not been studied. In this study, we identify the 401-462 and 551-661 coiled-coils as the regions in Rabex-5 and Rabaptin-5, respectively, that interact with one another. We also demonstrate that Rabex-5 undergoes ubiquitination and binds ubiquitin, though not via its proposed C-terminal CUE-like domain. Instead, the N-terminal region of Rabex-5 (residues 1-76), comprising an A20-like Cys2/Cys2 zinc finger and an adjacent α-helix, is important for ubiquitin binding and ubiquitination. Importantly, we demonstrate that the Rabex-5 zinc finger displays ubiquitin ligase (E3) activity. These observations extend our understanding of the regulation of Rabex-5 by Rabaptin-5. Moreover, the demonstration that Rabex-5 is a ubiquitin ligase that binds ubiquitin and undergoes ubiquitination indicates that its role in endosome fusion may be subject to additional regulation by ubiquitin-dependent modifications.